DIGITAL INKLUSI PEDESAAN: MENJEMBATANI SOLUSI MARGINALISASI INFORMASI DAN LAYANAN ADMINISTRASI - Waliyuddin (Journal of Media and Communication Studies, 2025)
Rural digital inclusion is a concept that prioritizes the utilization of information technology transformation from analog to digital systems. It is an innovation that enhances inclusivity to achieve equality in quality of life as well as access to information and administrative services in rural areas. This study aims to examine the factors contributing to the gap, bridge development efforts, and identify the challenges faced in digital development by village governments through e-government in Lembang Bo’ne Buntu Sisong, Makale Selatan District, Tana Toraja Regency. The results show that the digital gap is caused by limited infrastructure, lack of access skills, and unavailability of budget. Digital inclusion initiated by the lembang government serves as a solution to anticipate conditions of information marginalization by developing a village/lembang website that can effectively and efficiently fulfill the community’s right to information and public services. The challenges faced in developing digitalization in the lembang government or e-government include: (1) leadership challenges related to policy support and regulations for the implementation of e-government; (2) cultural challenges among villagers in accepting the transformation of information access and services from analog to digital, where available access has not been used participatively and awareness of its utilization is still low; and (3) governance challenges, as the transformation of information and administrative services in an e-government system requires competence support from village government officials. The findings of this study are expected to provide insights into implementing digital inclusion to minimize the emergence of marginalized groups due to the digital divide.